CULTURE, CIVILIZATION AND NATIONALISM: CULTURAL DISCUSSION OF 'SANSKRITI KE CHAR ADHYAY' BY DINKAR - Kumar, Priyanshu (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Ramdhari Singh 'Dinkar's' work 'Sanskriti Ke Char Adhyay' is an in-depth study focused on Indian culture, civilization and nationalism. In this book, Dinkar has presented his views on the historical development of Indian culture, its traditions, and the balance between modernity. Clarifying the difference between culture and civilization, he has written that culture is a symbol of the moral and spiritual values ​​of human life, while civilization is a symbol of material progress and technological development. Dinkar considered the tolerance, coordination, and diversity of Indian culture as its greatest strength. Presenting it as the identity of Indian nationalism, he said that Indian culture is a confluence of various religions, traditions, and ideas. This work outlines the development of Indian culture in four stages—primitive, Vedic, Buddhist, and modern. This paper does a cultural analysis of this work of Dinkar and attempts to apply his ideas with relevance in the current social context. This book of Dinkar is not only a mirror of Indian culture, but it is also a source of inspiration for cultural and national unity. His ideology is equally relevant in today's social and cultural context.